International Power Interconnections : Moving from Electricity Exchange to Competitive Trade - Charpentier, J. P. (World Bank, Washington, DC, 2012)
International electricity markets are complex, and experience with them is limited. Purely physical exchange between countries already occurs where interconnection lines are in place. But power trade requires more sophisticated organizational structures and coordination. Harmonizing national organizational structures is a first step toward the freer flow of power across borders. Unbundling national power sectors could help further in breaking bottlenecks, particularly in transmission. But coordination needs much attention. Here, the key issue for policymakers is this: What terms and conditions are needed to establish competitive regional electricity trade in which buyers and seller can, at any time and regardless of their locations, negotiate power and energy contracts covering a wide spectrum of commercial products? This Note states that, strictly speaking, there is still no electricity trade in the full sense. To achieve true electricity trade, these are the prerequisites: need and willingness, technical means, national institutions and regional operations, and pricing and contractual issues.